2017
DOI: 10.3390/c3030021
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenes in Electrochemical Catalytic and Affinity Biosensing: A Review

Abstract: Nanotechnology is becoming increasingly important in the field of (bio)sensors. The performance and sensitivity of electrochemical biosensors can be greatly improved by the integration of nanomaterials into their construction. In this sense, carbon nanomaterials have been widely used for preparation of biosensors due to their ability to enhance electron-transfer kinetics, high surface-to-volume ratios, and biocompatibility. Fullerenes are a very promising family of carbon nanomaterials and have attracted great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Fullerene-based nanomaterials have been exploited for biomedical application, and different studies have revealed their biocompatibility with living organisms. It has been used as a bioreceptor as well as a biosensor and also exploited in biomedical engineering, and it has been reported to be biocompatible with living systems [6569]. The fullerene is a nontoxic material which can be exploited for filtration, adsorbents, and membrane stuff for environmental and water treatment applications.…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…Fullerene-based nanomaterials have been exploited for biomedical application, and different studies have revealed their biocompatibility with living organisms. It has been used as a bioreceptor as well as a biosensor and also exploited in biomedical engineering, and it has been reported to be biocompatible with living systems [6569]. The fullerene is a nontoxic material which can be exploited for filtration, adsorbents, and membrane stuff for environmental and water treatment applications.…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…A broad spectrum of compounds that find applications in healthcare diagnosis and POC analysis of diseases can be detected with such biosensor materials [22]. Carbon allotrope-based nanomaterials consisting of fullerenes, [23,24,25,26,27] nanotubes (CNT) [28,29,30,31,32,33], films of graphene and its derivatives [34,35,36,37], quantum dots [38,39,40,41], and nanodiamonds [42,43,44,45,46,47] play a substantial role in recent advancements in the biosensor domain. In addition to greater sensitivity and novel mechanisms, such sensors offer a higher spatial resolution in case of localised detection along with real-time and label-free non-destructive sensing.…”
Section: Carbon Allotrope-based Nanomaterials Applications In Healtmentioning
confidence: 99%
“…The effectiveness of enzymatic biosensors is determined by the achievement of an efficient electron transport between redox proteins and electrodes. Due to their complex structures and the deeply buried ligand binding sites of proteins, it is a challenge to achieve direct electron transfer between the redox proteins and the electrode surface [ 129 ]. In addition, redox proteins become irreversibly denatured when adsorbed on the electrode surface [ 119 ].…”
Section: Fullerenes For Electrochemical Biosensorsmentioning
confidence: 99%